Unveiling the efficacy of paroxetine and gabapentin in ulcerative colitis patients in remission with co-existing IBS-like symptoms: a single-blinded randomized clinical trial - Safaei, Farahnaz; Shahrokh, Shabnam; Naderi, Nosratollah; Rastegar, Reyhaneh; Shamsi, Alireza (Frontiers in Medicine, 2024)
Introduction This clinical trial is designed to explore the efficacy of paroxetine and gabapentin in alleviating functional gastrointestinal symptoms, anxiety, depression, and quality of life in patients with ulcerative colitis during the remission stage. Methods The study enrolled 97 patients with ulcerative colitis in remission who had reported functional gastrointestinal symptoms. Patients were measured in terms of quality of life, anxiety, depression, and IBS severity. One group received paroxetine at a dosage of 20 mg/day, and the other group received gabapentin at a dosage of 100 mg/day in the first month and 300 mg/day in the second and third months. The patients were followed up for 3 months. Results Anxiety (p < 0.001), depression (p = 0.012), and severity score levels (p = 0.045) among patients in the paroxetine group were significantly lower compared to the gabapentin group following the intervention. Paired evaluation in each treatment group revealed a significant reduction in the paroxetine group, while changes in the gabapentin group were not significant. Quality-of-life scores among patients in the paroxetine group were significantly higher compared to the gabapentin group following the intervention (p < 0.001). Conclusion The rate of improvement in gastrointestinal functional symptoms, anxiety, depression, and quality of life is significantly superior with paroxetine compared to gabapentin. Clinical trial registration https://irct.behdasht.gov.ir/trial/69397, identifier RCT20220417054557N1.